Evaluation and distribution of essential minerals in different soil habitats of cold arid high-altitude environments - Guru Charan; Vijay K. Bharti; Jatinder Kumar; Rajendra kumar; Preeti Mahawar; Bijendra Kumar (Discover Sustainability)
Abstract Essential minerals are fundamental components of soil ecosystems, directly impacting soil health and subsequently influencing the nutritional quality of feed/forages for livestock. Hence, this study aimed to investigate essential mineral nutrients in various soil ecosystems in the cold arid region of of Leh-Ladakh, India, situated under the Tibetan plateau and part of the Trans-Himalayas. For the study, soil samples were collected from different areas including agricultural soil, pasture land, and Indus River sediment, and analyzed for iron (Fe), Magnesium (Mg), Manganese (Mn), Zinc (Zn), Copper (Cu), Cobalt (Co) and Boron (B). The results revealed varying concentrations of these minerals across different soil types. Total mean concentrations of Fe, Mg, and Mn were found as 32,027 ± 2026, 36,099 ± 1062, 32,068 ± 1787 ppm; 6325 ± 585, 3249 ± 337, 4416 ± 313 ppm; 583.33 ± 34.21, 582.99 ± 20.71, 661.28 ± 118.77 ppm in pasture land, Indus River sediment, and roadside soils respectively. Whereas Zn, Cu, Co, and Bo mean concentrations were observed as 84.87 ± 7.91, 79.14 ± 4.39 191.86 ± 143.95 ppm; 28.60 ± 2.6, 33.7 ± 1.7, 119 ± 92.6 ppm; 23.4 ± 2.1, 36.4 ± 2.3, 121 ± 118 ppm; 80.00 ± 7.10, 36.40 ± 2.50, 151.6 ± 104 ppm respectively in pasture land, roadside soil and Indus (river) sediments. Overall, the study found that Fe, Mg, Mn, Zn, Cu, Co, and B concentrations were within typical ranges for soil, indicating that essential mineral nutrients in various soil ecosystems of cold arid regions meet the requirements of crop plants and livestock.